Adaptable autocrats regime power in Egypt and Syria - Stacher, Joshua 1975- (American University in Cairo Press, 2012)
Joshua Stacher examines how executive power is structured in each country to show how these preexisting power configurations shaped the uprisings and, in turn, the outcomes. Presidential power in Egypt was centralized. Even as Mubarak was forced to relinquish the presidency, military generals from the regime were charged with leading the transition. The course of the Syrian uprising reveals a key difference: the decentralized character of Syrian politics. Only time will tell if Asad will survive in office, but for now, the regime continues to unify around him. While debates about election timetables, new laws, and the constitution have come about in Egypt, bloody street confrontations continue to define Syrian politics-the differences in authoritarian rule could not be more stark.